Are mass media campaigns effective in reducing drinking and driving? Systematic review – an update - Zatoński, Mateusz; Herbeć, Aleksandra (Journal of Health Inequalities, 2016)
Introduction: Data from the USA shows that of all the persons killed in traffic crashes approximately one-third die due to alcohol-impaired driving. In an attempt to tackle this mounting death toll, in the past several decades policy-makers have increasingly relied on mass media campaigns. These campaigns involve delivery of educational messages through one or more media channels. However, despite over six decades of research, little consensus exists regarding the efficacy of such interventions. A recent comprehensive meta-analysis of 67 studies by Phillips and colleagues (published in 2011) assessed the effect of road safety campaigns on accidents, including campaigns against alcohol-impaired driving (AID). It has, however, only included studies published up until 2007. Aim of the study : To update the review conducted by Phillips and colleagues with studies published between 2007 and 2014, with a focus on assessing whether mass media campaigns are helpful in preventing AID. Material and methods: MEDLINE and EMBASE databases were systematically searched on 13.03.2014. Results and conclusions : Four US-based studies met the inclusion criteria. The identified studies were generally of moderate quality. All four included self-reported AID as their measure, and this was selected as the primary outcome for the present review. Across the four studies, the mean decrease in self-reported AID was about 2%. The reviewed studies indicate that under some conditions, and with careful design and good execution, and preferably with a focus on positive messages, mass-media campaigns can successfully contribute to the reduction in AID. Nevertheless, some of the methodological shortcomings and challenges that characterise research on mass media campaigns and AID, and their focus on US-based populations, indicate that further rigorous studies in this area are needed.